Enhanced production of bio-indigo in engineered Escherichia coli, reinforced by cyclopropane-fatty acid-acyl-phospholipid synthase from psychrophilic Pseudomonas sp. B14-6 - Ham, Sion; Cho, Do Hyun; Oh, Suk Jin; Hwang, Jeong Hyeon; Kim, Hyun Jin; Shin, Nara; Ahn, Jungoh; Choi, Kwon Young; Bhatia, Shashi Kant; Yang, Yung Hun (Journal of Biotechnology, 2023)
Indigo dye is an organic compound with a distinctive blue color. Most of the indigo currently used in industry is produced via chemical synthesis, which generates a large amount of wastewater. Therefore, several studies have recently been conducted to find ways to produce indigo eco-friendly using microorganisms. Here, we produced indigo using recombinant Escherichia coli with both an indigo-producing plasmid and a cyclopropane fatty acid (CFA)-regulating plasmid. The CFA-regulating plasmid contains the cfa gene, and its expression increases the CFA composition of the phospholipid fatty acids of the cell membrane. Overexpression of cfa showed cytotoxicity resistance of indole, an intermediate product formed during the indigo production process. This had a positive effect on indigo production and cfa originated from Pseudomonas sp. B 14–6 was used. Optimal conditions for indigo production were determined by adjusting the expression strain, culture temperature, shaking speed, and isopropyl β-D-1-thiogalactopyranoside concentration. Treatment with Tween 80 at a particular concentration to increase the permeability of the cell membrane had a positive effect on indigo production. The strain with the CFA plasmid produced 4.1 mM of indigo after 24 h of culture and produced 1.5-fold higher indigo than the control strain without the CFA plasmid that produced 2.7 mM.
Keywords: Cyclopropane fatty acids; Cyclopropane-fatty acid-acyl-phospholipid synthase; Engineered escherichia coli; Flavin containing monooxygenase; Indigo; Indigo dye; Pseudomonas sp; Synthases; Tryptophanase; Acids; Cyclopropanes; Escherichia coli; Fatty Acids; Indigo Carmine; Phospholipids; Pseudomonas; Cyclopropane fatty acids; Cyclopropane-fatty acid-acyl-phospholipid synthase; Flavin-containing monooxygenase; Indigo; Tryptophanase